Theoretical Evaluation of Pluralism Concept in Architecture - Aya Shukri Mohammed; Kadhim Fathel Khalil (Kurdistan Journal of Applied Research)
Pluralism as a manifestation of the universe and nature that is felt and understood by all human beings is not a new idea, but rather it could identify as a divine principle and eternal, Pluralism applies in all creation fields, especially in architecture, this paper discusses the term of pluralism in different fields such as philosophy, linguistic, literacy, art, until it reaches to the architectural field, and discusses the effect of the term in architecture. The aim is to understand pluralism with its different branches and determine the indicators of the term in architecture. Studies that discussed the concept of pluralism are taken as case studies to reach the goal. As a result, it appeared that pluralism has several types, and each type is associated with indicators. In conclusion, these types are arranged under five levels and each type led to a specific feature in architecture.